Survey on Organizational Culture Based on the Denison Model; Case Study Tehran University of Medical Sciences - niloufar amiri ghale rashidi; alireza namazi shabestari; alireza arab yarmohammadi; maryam mazinani; sepideh masoud sinaki (Tehran University of Medical Sciences, 2019)
Background & Aim: The purpose of this study was to investigate the current organizational culture in Tehran University of Medical Sciences, which is to be considered in order to strengthen organizational culture.   Material & Method: The present study is a descriptive cross-sectional study and an applied research-based survey that was conducted in Tehran University of Medical Sciences in 2019. The sample size was calculated and analyzed using Cochranchr('39')s formula for 306 people. In this study, Denisonchr('39')s Organizational Culture Questionnaire was used to collect data. Data were analyzed using SPSS software, descriptive statistical methods, one-sample mean and Pearson Correlation Tests.   Results: The average of organizational culture in Tehran University of Medical Sciences, in each component, culture of Involvement (2.29), culture of consistency (2.63), culture of adaptability (2.66) and culture of mission (2.58), Which represented a higher-than-average culture in all aspects of Denisonchr('39')s view.   Conclusion: The organization should do some corrective actions with respect to the components of adaptability (subculture of organizational learning) and Involvement (Capability Development), which has earned a lower score.